The Effect Of Drinking Sirsak Leaves (Annona Muricata Linn) On Reducing Blood Pressure In Menopause Women With Hipertension - Telova, Yurizki; Simarmata, Pratiwi Christa; Damayanti (JURNAL KEBIDANAN KESTRA (JKK), 2024)
Hypertension or high blood pressure is a disorder of the blood vessels that results in the supply of oxygen and nutrients carried by the blood being obstructed to the body's tissues. Hypertension is often referred to as the Silent Killer, because it is a dark killer disease without being accompanied by symptoms first. Soursop leaf (Annona Muricata Linn) is a traditional medicine used as a therapy for hypertension, the content of soursop leaves which is thought to reduce blood pressure is potassium ions. High potassium levels can increase sodium excretion, as a result it can reduce blood volume & blood pressure. Menopause in women is associated with the depletion of ovarian follicles accompanied by physical and psychological changes. One of the comorbidities often experienced by menopausal women is hypertension. The purpose of this study was to determine the effect of soursop leaf decoction on lowering blood pressure in menopausal women with hypertension. This type of research is a quasi experiment (quasi experimen). This study uses a one group pretest-postest design, which is a treatment design using only the experimental group without a comparison or control group. Based on the results of the study seen from 15 respondents obtained with the Wilcoxon test results, it can be seen that the resulting p-value is 0.000. This means that p < (a = 0.05), this shows that there are changes in blood pressure in wa.